(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2019)
The aim of this research is to highlight the most important risks facing Islamic banks resulting from the granting of bank credit، namely the credit risk and the resulting effects، especially their regarding to the profitability of banking through the measurement and analysis of credit risk. Two Islamic banks were selected، National Islamic Bank and Elaf Islamic bank we use The indicators of credit risk and bank profitability and we explain the most important problems of both banks were used as a result of credit risks and their effects on bank profitability، these indicators were analyzed and then tested by a test F، P-Value and impact statement by the coefficient of determination R2 using analysis of variance (ANOVA) The research concluded that there is a significant effect of credit risk indicators on profitability on which was accept the alternative hypothesis ، The study also reached the recommendations of the most important interest in the formation of the necessary allocations (provision for doubtful debts) and be based on the correct basis to be able meet any risk.